Gymnastics as a tool for social cohesion_reimagining the Sports Facility along Klipfontein Road - Smith, Chelsea (School of Architecture, Planning and Geomatics, 2023)
This dissertation sets to explore and interrogate the role of well-integrated public social space and reimagining the sport facility in a post-Apartheid city. It highlights an issue of access to well-resourced sport facilities as a result of apartheid spatial planning affecting marginalised communities. It will investigate the role of sport and social space in an urban context. This thesis aims to highlight the significance of sport and public space which is integrated into the urban fabric – and use a national gymnastics school as a part of this social integration through an architectural response. The outcome of this research will look to an appropriate architectural response which can promote connections between residents, school goers and commuters through Athlone. It will contribute to a reimagined intensified edge of Klipfontein Road with mixed-uses as an urban proposal. I will explore how a national sports facility can positively add to the urban landscape as a landmark whilst being incorporated into a carefully designed public precinct. My response to the architectural and social aspects of social revitalisation through sport will be developed through the exploratory study of concepts, literature, theories, relevant precedents, case studies and technical studies will justify the appropriate design development.